Development of E-modules Based on Quantum Learning in Projek IPAS for Class X Vocational High School - Betty Deviana; Zelhendri Zen; Rayendra; Fetri Yeni J; Emilham Mirshad; Abdul Habib Arrasyidi Desky (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a Quantum Learning-based e-module for the subject of Natural and Social Science Projects (IPAS) in class X Vocational High School, focusing on Economic Behavior and Social Welfare material. The development employed the ADDIE model (analysis, design, development, implementation, and evaluation). Expert validation results show that the e-module is very valid in material (89.70%) and language (96.70%), and valid in media (78%). Practicality tests indicate the module is practical (79% by teachers) and very practical (82% by students). Effectiveness was assessed through pre-test and post-test with 31 students, analyzed using the t-test. The results show a t-count of 16.17, exceeding the t-table value of 1.697 at a 0.05 significance level, indicating a significant improvement in student learning outcomes after using the module. In conclusion, the Quantum Learning-based e-module meets the criteria of validity, practicality, and effectiveness, and can be used as a quality learning resource to enhance student engagement and achievement.